Reproductive justice : the politics of health care for Native American women - Gurr, Barbara Anne (Rutgers University Press, 2015)
In Reproductive Justice, sociologist Barbara Gurr provides the first analysis of Native American women's reproductive healthcare and offers a sustained consideration of the movement for reproductive justice in the United States. The book examines the reproductive healthcare experiences on Pine Ridge Reservation, home of the Oglala Lakota Nation in South Dakota--where Gurr herself lived for more than a year. Gurr paints an insightful portrait of the Indian Health Service (IHS)--the federal agency tasked with providing culturally appropriate, adequate healthcare to Native Americans--shedding much-needed light on Native American women's efforts to obtain prenatal care, access to contraception, abortion services, and access to care after sexual assault. Reproductive Justice goes beyond this local story to look more broadly at how race, gender, sex, sexuality, class, and nation inform the ways in which the government understands reproductive healthcare and organizes the delivery of this care. It reveals why the basic experience of reproductive healthcare for most Americans is so different--and better--than for Native American women in general, and women in reservation communities particularly. Finally, Gurr outlines the strengths that these communities can bring to the creation of their own reproductive justice, and considers the role of IHS in fostering these strengths as it moves forward in partnership with Native nations.